Media image of the Russian Orthodox Church and the challenge of the pandemic - N. S. Zimova; E. V. Fomin (Цифровая социология, 2022)
In the digital age, social media have become especially relevant in creating the image of the Russian Orthodox Church. They have their own characteristics and provide a different image of Orthodoxy in comparison to traditional media.The article presents the results of a study of the media image of the Russian Orthodox Church during the coronavirus lockdown in Russia from January 3 to April 30, 2020. We used a social media analysis system “Kribrum”. At the first stage, content on the Russian Orthodox Church and coronavirus was analysed, and the top 35 influential media were compiled. Taking into account the political attitude of the media, they were divided into state (conservative), neutral (without an editorial agenda); oppositional (liberal). The rating did not include Orthodox media, which indicates the low influence of the Church on the consciousness of users. The basis of the information space is formed by non-religious and opposition media with high ratings. At the second stage, with using the method of content analysis, the image of the Russian Orthodox Church and its constituent elements were analysed – the image of the Orthodox faith, the Patriarch, priests, believers. Two poles are highlighted, between which the images of the Russian Orthodox Church are built. In the state media, the Russian Orthodox Church is presented as a state institution, a patriotic organisation uniting all Orthodox Christians. It performs a psychological function and helps believers to survive the period of a pandemic through prayers. Oppositional (liberal) media show the Russian Orthodox Church as an archaic, self-serving and pro-government organisation that has turned out to be unable to prepare for a pandemic and to make the right decisions so that believers do not get coronavirus. Rhetorical, technical and analytical (social technologies) methods of framing the image of the Russian Orthodox Church are revealed.It can be argued that the Internet is dominated by a stereotypical negative and distorted image of the Russian Orthodox Church. This leads to a violation of the understanding of the social functions of the Church and a decrease in its role in public life.